Analisis Link Budget Penyambungan Serat Optik Menggunakan Optical Time Domain Reflectometer AQ7275 (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
An optical fiber is a high-speed telecommunication transmission medium. Principally, an optical fiber is made of a very fine glass fiber material, which is able to transmit light waves using light reflection method on the surface of the fiber optics core. An underground installation of the fiber optics makes this device robust from external interferences. However, the fiber optic cable performance should always be checked to maintain performance during data transmission process. One way to test fiber optics cable performance is by using an Optical Time - Domain Reflectometer (OTDR) device. This device sends a light wave from one point of the fiber optics cable. The light wave then returns when reaching the other point of the fiber optic cable while carrying some measurement parameters especially the physical length and attenuation of a fiber optic cable. The evaluation of the fiber optics cable performance requires the preparation, installation, and configuration of the OTDR. In this paper, we conducted evaluation on the performances of fiber optics cable. The data generated by the performed evaluation indicated an occurring attenuation on the fiber optics cable along 64.402 km of its lengths.